1986
DOI: 10.1007/bf00026667
|View full text |Cite
|
Sign up to set email alerts
|

Sediments and sedimentary history of Lake Attersee (Salzkammergut, Austria)

Abstract: Attersee represents a good example of a lake situated in the Northern forelands of the Northern Calcareous Alps and influenced by different sediment-supplying processes during the postglacial . Several compounds, of different origin, form the sediments of the basin . Clastics which are mainly composed of dolomites derive from the Northern Calcareous Alps . Clastic input of organic and inorganic particles is accomplished by rivers and landslides . They are responsible for the main input of siliciclasts like qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The abundance of C. tricuspis has been linked with organic rich substrates and eutrophic conditions (Collins et al, 1990;Patterson et al, 2013). Several studies have suggested a link between elevated Ca concentrations and enhanced lake productivity (Otsuki & Wetzel, 1974;Kelts & Ksü, 1978;Behbehani et al, 1986). Therefore, the increase in C. tricuspis coupled and with a general increase in the faunal diversity and numbers of healthy lake-indicating taxa in HC may be indicative of enhanced lake productivity in the southern part of the lake.…”
Section: Frame Lakementioning
confidence: 99%
“…The abundance of C. tricuspis has been linked with organic rich substrates and eutrophic conditions (Collins et al, 1990;Patterson et al, 2013). Several studies have suggested a link between elevated Ca concentrations and enhanced lake productivity (Otsuki & Wetzel, 1974;Kelts & Ksü, 1978;Behbehani et al, 1986). Therefore, the increase in C. tricuspis coupled and with a general increase in the faunal diversity and numbers of healthy lake-indicating taxa in HC may be indicative of enhanced lake productivity in the southern part of the lake.…”
Section: Frame Lakementioning
confidence: 99%
“…Two main explanations are possible: (a) the shells were dissolved after deposition and (b) the ion concentration in the lake water was strongly diluted because of enhanced runoff from the Lake Trasimeno catchment where limestones are absent. Examples of shell decalcification because of high lake productivity are reported at Lake Lansing, MI, US, (McNabb, 1979), Lake Attersee, Austria (Behbehan et al, 1986), at the Eifel maar lakes, Germany (Scharf, 1993), and at Preola and Gorgo Basso lakes, Sicily (Curry et al, 2016). The last authors suggest that shell dissolution could be because of both low Ca 2 + water concentration and to elevated levels of dissolved CO 2 as a result of increased primary productivity and organic matter decomposition.…”
Section: Palaeoenvironmental/palaeoclimate Interpretationmentioning
confidence: 99%